DIGITAL TRANSFORMATION OF AGRICULTURAL COOPERATIVES: SERVICE INNOVATION AND ITS IMPACT ON MILLENNIAL FARMERS' INCOME IN EAST JAVA - Reni Jasmin Ardiana Indradiartha (CV. Radja Publika, 2025)
This study aims to analyze the digital transformation of agricultural cooperatives, the use of their service innovations, and their impact on the income of millennial farmers in East Java. The study used a descriptive-correlational quantitative approach with a sample of 100 millennial farmers who were members of digital cooperatives selected through purposive sampling. Data were collected through questionnaires, interviews, and documentation, then analyzed using descriptive statistics, Pearson correlation, and linear regression. The results showed that the majority of respondents were 26–35 years old with secondary to university education levels, and had been a member of digital cooperatives for an average of two years. The most widely used service innovations include online transactions of production facilities, real-time market price information, and crop yield monitoring. The digital transformation of cooperatives has a positive impact on farmers' incomes, with an average increase of 23.5% after one year of using digital services. The increase was driven by distribution efficiency, reduced transaction costs, and wider market access. These findings confirm that the digitalization of agricultural cooperatives not only improves efficiency and transparency, but also plays a significant role in empowering millennial farmers' economies towards sustainable modern agriculture.